Impacts of Quaternary Climate History on the Biogeography of Specialized Butterflies in the Great Basin of North America - Sarah B. Bialik; Joseph S. Wilson; Michelle Sneck; Dennis D. Murphy; James A. Fordyce; Katherine L. Bell; Matthew L. Forister; Chris C. Nice (Journal of Biogeography, 2026)
Aim Dramatic Quaternary climate fluctuations impacted the evolutionary history and contemporary biogeography of many residents of the Great Basin Desert of western North America. This study investigates the historical biogeographic processes that shaped the contemporary distribution of genetic variation in a polytypic group of specialized butterflies that are residents of unique dune and playa habitats. Many of the subspecies are considered to be threatened and this study uses high‐resolution SNP data to understand their history and quantify patterns of differentiation to inform conservation. Location Great Basin, western North America. Taxon The pallid dotted blue butterfly complex ( Euphilotes pallescens , Lycaenidae). Methods We constructed reduced‐representation genomic libraries to generate population genomics data that were used in clustering, ordination, and phylogenetic analyses. Pairwise differentiation between localities was quantified and the relationship between genomic differentiation and geography was analysed using a linear model. In addition, an estimated effective migration surface illustrated geographic patterns of genomic variation. Results Euphilotes pallescens populations were clearly differentiated from congeneric species and several subspecies, especially in the northwestern portion of the sampled range, were identifiable from genomic variation. When geographic distance was controlled, genetic differentiation was greatest between populations of Eu. pallescens compared to congeners, and within Eu. pallescens , northwestern populations were more differentiated than southern populations. The estimated effective migration surface also showed greater areas of reduced gene flow in the northwestern region. Main Conclusions Euphilotes pallescens comprises isolated populations on dune habitats in the Great Basin. Populations in the northwestern region are especially isolated and their patterns of genetic variation are consistent with the history of climate change and ancient pluvial lakes that occupied much of this region at intervals during the Quaternary. These butterflies are members of unique, localized communities whose persistence requires protections from anthropogenic threats, especially habitat loss including from recreation and off‐road vehicles in sensitive habitats.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

A novel tissue culture model for evaluating the effect of aging on stem cell fate in adult microvascular networks - Mohammad S. Azimi; Jessica M. Motherwell; Maria Dutreil; Ryan L. Fishel; Matthew Nice; Nicholas A. Hodges; Bruce A. Bunnell; Adam Katz; Walter L. Murfee (GeroScience, 2020)

Extreme heterogeneity of population response to climatic variation and the limits of prediction - Chris C. Nice; Matthew L. Forister; Joshua G. Harrison; Zachariah Gompert; James A. Fordyce; James H. Thorne; David P. Waetjen; Arthur M. Shapiro (Global Change Biology, 2019)
Certain general facets of biotic response to climate change, such as shifts in phenology and geographic distribution, are well characterized; however, it is not clear whether the observed similarity of responses across taxa will extend to variation in other population‐level processes. We examined population response to climatic variation using long‐term incidence data (collected over 42 years) encompassing 149 butterfly species and considerable habitat diversity (10 sites along an elevational gradient from sea level to over 2,700 m in California). Population responses were characterized by extreme heterogeneity that was not attributable to differences in species composition among sites. These results indicate that habitat heterogeneity might be a buffer against climate change and highlight important questions about mechanisms maintaining interpopulation differences in responses to weather. Despite overall heterogeneity of response, population dynamics were accurately predicted by our model for many species at each site. However, the overall correlation between observed and predicted incidence in a cross validation analysis was moderate (Pearson's r = 0.23, SE 0.01), and 97% of observed data fell within the predicted 95% credible intervals. Prediction was most successful for more abundant species as well as for sites with lower annual turnover. Population‐level heterogeneity in response to climate variation and the limits of our predictive power highlight the challenges for a future of increasing climatic variability.

The predictability of genomic changes underlying a recent host shift in Melissa blue butterflies - Samridhi Chaturvedi; Lauren K. Lucas; Chris C. Nice; James A. Fordyce; Matthew L. Forister; Zachariah Gompert (Molecular Ecology, 2018)
Despite accumulating evidence that evolution can be predictable, studies quantifying the predictability of evolution remain rare. Here, we measured the predictability of genome‐wide evolutionary changes associated with a recent host shift in the Melissa blue butterfly ( Lycaeides melissa ). We asked whether and to what extent genome‐wide patterns of evolutionary change in nature could be predicted (i) by comparisons among instances of repeated evolution and (ii) from SNP × performance associations in a laboratory experiment. We delineated the genetic loci ( SNP s) most strongly associated with host use in two L. melissa lineages that colonized alfalfa. Whereas most SNP s were strongly associated with host use in none or one of these lineages, we detected a an approximately twofold excess of SNP s associated with host use in both lineages. Similarly, we found that host‐associated SNP s in nature could also be partially predicted from SNP × performance (survival and weight) associations in a laboratory rearing experiment. But the extent of overlap, and thus degree of predictability, was somewhat reduced. Although we were able to predict (to a modest extent) the SNP s most strongly associated with host use in nature (in terms of parallelism and from the experiment), we had little to no ability to predict the direction of evolutionary change during the colonization of alfalfa. Our results show that different aspects of evolution associated with recent adaptation can be more or less predictable and highlight how stochastic and deterministic processes interact to drive patterns of genome‐wide evolutionary change.

Understanding a migratory species in a changing world: climatic effects and demographic declines in the western monarch revealed by four decades of intensive monitoring - Anne E. Espeset; Joshua G. Harrison; Arthur M. Shapiro; Chris C. Nice; James H. Thorne; David P. Waetjen; James A. Fordyce; Matthew L. Forister (Oecologia, 2016)

Quantifying diet breadth through ordination of host association - J. A. Fordyce; C. C. Nice; C. A. Hamm; Matthew L. Forister (Ecology, 2016)
Many areas of research in ecology and evolutionary biology depend on the quantification of dietary niche width. For herbivorous insects, diet breadth has most often been measured as simply the number and type of host plant taxa attacked. We propose an index of host range (which we refer to as “ordinated diet breadth”) based on observed associations between plants and insects, and the calculation of multivariate distances among plants in ordination space. Similarities and distances are calculated based on host association and, in this context, potentially encompass multiple properties of plants, including phytochemistry, phenology, and other plant traits. This approach can distinguish between herbivores that utilize suites of hosts that are commonly used together and herbivores that attack unusual host combinations, and thus have a relatively broad diet breadth. For illustration, we use a data set of nymphalid butterfly host records, and compare taxonomic and ordinated host range. For a large number of butterfly taxa, we find that host use is clustered in multivariate space with respect to associations observed across all of the butterfly taxa. Applications are discussed, including a hypothesis test of nonrandom host association, and prediction of shifts and expansions of diet breadth.

Regional population differentiation in the morphologically diverse, elevationally widespread Nearctic skipper Polites sabuleti - Joshua P. Jahner; Matthew L. Forister; Chris C. Nice; James A. Fordyce; Joseph S. Wilson; Dennis D. Murphy; Zachary H. Marion; Arthur M. Shapiro (Journal of Biogeography, 2015)
Aim To evaluate three phylogeographical models associated with the presence of mountains (montane vicariance, sky island and parapatry) as drivers of intraspecific diversification in the sandhill skipper, Polites sabuleti (Lepidoptera: Hesperiidae), a morphologically variable species found in a variety of habitats from sea level to the alpine zone. Location Western North America. Methods The mitochondrial cytochrome c oxidase subunit II region was sequenced in 189 P. sabuleti individuals. Mitochondrial sequences were used in a spatial analysis of molecular variance ( SAMOVA ) to evaluate geographical population structure. AFLP markers were also generated for 347 individuals in order to estimate admixture proportions and examine population differentiation based on the nuclear genome. Results Twenty‐five mitochondrial haplotypes and 42 anonymous AFLP loci were found across 36 collection localities. Mitochondrial variation suggests a degree of regional population structure, although at least one of the inferred population groups extends over nearly the entire geographical range of the species. Analyses of nuclear data ( AFLP s) identified five genetic clusters, including one restricted to high elevations in the Sierra Nevada. Main conclusions The distribution of genetic variation within Polites sabuleti , a species with a broad elevational range, does not strictly support either mountain‐associated vicariance or ‘sky island’ isolation as the dominant process. Instead, we find complex population structure, including evidence for divergence between high‐ and low‐elevation populations in the Sierra Nevada mountains.

The evolution of novel host use is unlikely to be constrained by trade‐offs or a lack of genetic variation - Zachariah Gompert; Joshua P. Jahner; Cynthia F. Scholl; Joseph S. Wilson; Lauren K. Lucas; Victor Soria‐Carrasco; James A. Fordyce; Chris C. Nice; C. Alex Buerkle; Matthew L. Forister (Molecular Ecology, 2015)
The genetic and ecological factors that shape the evolution of animal diets remain poorly understood. For herbivorous insects, the expectation has been that trade‐offs exist, such that adaptation to one host plant reduces performance on other potential hosts. We investigated the genetic architecture of alternative host use by rearing individual Lycaeides melissa butterflies from two wild populations in a crossed design on two hosts (one native and one introduced) and analysing the genetic basis of differences in performance using genomic approaches. Survival during the experiment was highest when butterfly larvae were reared on their natal host plant, consistent with local adaptation. However, cross‐host correlations in performance among families (within populations) were not different from zero. We found that L. melissa populations possess genetic variation for larval performance and variation in performance had a polygenic basis. We documented very few genetic variants with trade‐offs that would inherently constrain diet breadth by preventing the optimization of performance across hosts. Instead, most genetic variants that affected performance on one host had little to no effect on the other host. In total, these results suggest that genetic trade‐offs are not the primary cause of dietary specialization in L. melissa butterflies.

Admixture and the organization of genetic diversity in a butterfly species complex revealed through common and rare genetic variants - Zachariah Gompert; Lauren K. Lucas; C. Alex Buerkle; Matthew L. Forister; James A. Fordyce; Chris C. Nice (Molecular Ecology, 2014)
Detailed information about the geographic distribution of genetic and genomic variation is necessary to better understand the organization and structure of biological diversity. In particular, spatial isolation within species and hybridization between them can blur species boundaries and create evolutionary relationships that are inconsistent with a strictly bifurcating tree model. Here, we analyse genome‐wide DNA sequence and genetic ancestry variation in Lycaeides butterflies to quantify the effects of admixture and spatial isolation on how biological diversity is organized in this group. We document geographically widespread and pervasive historical admixture, with more restricted recent hybridization. This includes evidence supporting previously known and unknown instances of admixture. The genome composition of admixed individuals varies much more among than within populations, and tree‐ and genetic ancestry‐based analyses indicate that multiple distinct admixed lineages or populations exist. We find that most genetic variants in Lycaeides are rare (minor allele frequency

A hierarchical perspective on the diversity of butterfly species' responses to weather in the Sierra Nevada Mountains - Chris C. Nice; Matthew L. Forister; Zachariah Gompert; James A. Fordyce; Arthur M. Shapiro (Ecology, 2014)
An important and largely unaddressed issue in studies of biotic–abiotic relationships is the extent to which closely related species, or species living in similar habitats, have similar responses to weather. We addressed this by applying a hierarchical, Bayesian analytical framework to a long‐term data set for butterflies which allowed us to simultaneously investigate responses of the entire fauna and individual species. A small number of variables had community‐level effects. In particular, higher total annual snow depth had a positive effect on butterfly occurrences, while spring minimum temperature and El Niño‐Southern Oscillation (ENSO) sea‐surface variables for April–May had negative standardized coefficients. Our most important finding was that variables with large impacts at the community‐level did not necessarily have a consistent response across all species. Species‐level responses were much more similar to each other for snow depth compared to the other variables with strong community effects. This variation in species‐level responses to weather variables raises important complications for the prediction of biotic responses to shifting climatic conditions. In addition, we found that clear associations with weather can be detected when considering ecologically delimited subsets of the community. For example, resident species and non‐ruderal species had a much more unified response to weather variables compared to non‐resident species and ruderal species, which suggests local adaptation to climate. These results highlight the complexity of biotic–abiotic interactions and confront that complexity with methodological advances that allow ecologists to understand communities and shifting climates while simultaneously revealing species‐specific variation in response to climate.

Complex evolutionary history of the pallid dotted‐blue butterfly (Lycaenidae: Euphilotes pallescens ) in the Great Basin of western North America - Joseph S. Wilson; Michelle Sneck; Dennis D. Murphy; Chris C. Nice; James A. Fordyce; Matthew L. Forister (Journal of Biogeography, 2013)
Aim The aim of this study was to investigate patterns of genetic isolation associated with populations in discrete habitat patches in a North American cold desert through analysis of the pallid dotted‐blue butterfly, Euphilotes pallescens . This small butterfly is largely restricted to low‐elevation habitats across the Great Basin. The apparent geographical isolation and reported morphological variation among E. pallescens populations makes this species an ideal candidate with which to investigate patterns of genetic isolation and diversification in this arid region. Location Great Basin, western North America. Methods We used sequence data from nuclear and mitochondrial genes to investigate genetic diversity among E. pallescens populations, and among E. pallescens and a number of closely related Euphilotes species, using Bayesian phylogenetic analyses, as well as population genetic analyses. In conjunction with genetic variation, morphological variation was examined in the context of geographical and subspecific differentiation. Results Our genetic and morphological analyses suggest a moderate amount of isolation among populations, consistent with the hypothesis of restricted gene flow among isolated dune habitats, and possibly associated with isolation in distinct Pleistocene refugia. The patterns of diversification within E. pallescens and among closely related species are complicated by discordance among phylogenetic reconstructions based on nuclear and mitochondrial genes. Discordance among gene genealogies suggests a complex evolutionary history, perhaps involving alternating periods of reticulation and divergence in isolation. Main conclusions Although E. pallescens may be a vagile species, we find that persistence on isolated dunes in the Great Basin is associated with appreciable genetic and morphological differentiation among populations. However, genetic, morphological and taxonomic axes of variation are only partially in agreement. More generally, the discordance we find among genetic regions is consistent with the ascendant paradigm in phylogenetic reconstruction: gene genealogies often do not perfectly match species trees. Thus we present Euphilotes as a model for future biogeographical and phylogenetic reconstructions employing larger data sets of independent sequence markers.

Secondary contact between Lycaeides idas and L. melissa in the Rocky Mountains: extensive admixture and a patchy hybrid zone - Zachariah Gompert; Lauren K. Lucas; James A. Fordyce; Matthew L. Forister; Chris C. Nice (Molecular Ecology, 2010)

Bayesian analysis of molecular variance in pyrosequences quantifies population genetic structure across the genome of Lycaeides butterflies - ZACHARIAH GOMPERT; MATTHEW L. FORISTER; JAMES A. FORDYCE; CHRIS C. NICE; ROBERT J. WILLIAMSON; C. ALEX BUERKLE (Molecular Ecology, 2010)

Host range evolution is not driven by the optimization of larval performance: the case of Lycaeides melissa (Lepidoptera: Lycaenidae) and the colonization of alfalfa - Matthew L. Forister; Chris C. Nice; James A. Fordyce; Zachariah Gompert (Oecologia, 2009)

Widespread mito‐nuclear discordance with evidence for introgressive hybridization and selective sweeps in Lycaeides - ZACHARIAH GOMPERT; MATTHEW L. FORISTER; JAMES A. FORDYCE; CHRIS C. NICE (Molecular Ecology, 2008)
We investigated the extent and potential cause(s) of mitochondrial introgression within the polytypic North American Lycaeides species complex (Lepidoptera). By comparing population genetic structure based on mitochondrial DNA (COI and COII) and nuclear DNA (251 polymorphic amplified fragment length polymorphism markers), we detected substantial mito‐nuclear discordance, primarily involving a single mitochondrial haplotype (h01), which is likely due to mitochondrial introgression between differentiated Lycaeides populations and/or species. We detected reduced mitochondrial genetic diversity relative to nuclear genetic diversity in populations where mitochondrial haplotype h01 occurs, suggesting that the spread of this haplotype was facilitated by selection. We found no evidence that haplotype h01 is associated with increased fitness (in terms of survival to eclosion, fresh adult weight, and adult longevity) in a polymorphic Lycaeides melissa population. However, we did find a positive association between mitochondrial haplotype h01 and infection by the endoparasitic bacterium Wolbachia in one out of three lineages tested. Linkage disequilibrium between mitochondrial haplotype h01 and Wolbachia infection status may have resulted in indirect selection favouring the spread of haplotype h01 in at least one lineage of North American Lycaeides . These results illustrate the potential for introgressive hybridization to produce substantial mito‐nuclear discordance and demonstrate that an individual's mitochondrial and nuclear genome may have strikingly different evolutionary histories resulting from non‐neutral processes and intrinsic differences in the inheritance and biology of these genomes.

Considering evolutionary processes in the use of single-locus genetic data for conservation, with examples from the Lepidoptera - Matthew L. Forister; Chris C. Nice; James A. Fordyce; Zachariah Gompert; Arthur M. Shapiro (Journal of Insect Conservation, 2008)

Identifying units for conservation using molecular systematics: the cautionary tale of the Karner blue butterfly - ZACHARIAH GOMPERT; CHRIS C. NICE; JAMES A. FORDYCE; MATTHEW L. FORISTER; ARTHUR M. SHAPIRO (Molecular Ecology, 2006)
The federally endangered North American Karner blue butterfly ( Lycaeides melissa samuelis ) and the closely related Melissa blue butterfly ( L. m. melissa ) can be distinguished based on life history and morphology. Western populations of L. m. samuelis share mitochondrial haplotypes with L. m. melissa populations, while eastern populations of L. m. samuelis have divergent haplotypes. Here we test two hypotheses concerning the presence of L. m. melissa mitochondrial haplotypes in western L. m. samuelis populations: (i) mitochondrial introgression has occurred from L. m. melissa populations into western L. m. samuelis populations, or (ii) western populations of the nominal L. m. samuelis are more closely related to L. m. melissa than to eastern L. m. samuelis populations, yet are phenotypically similar to the latter. A Bayesian algorithm was used to cluster 190 L. melissa individuals based on 143 informative amplified fragment length polymorphism (AFLP) loci. This method clearly differentiated L. m. samuelis and L. m. melissa . Thus, genomic divergence was greater between western L. m. samuelis populations and L. m. melissa populations than it was between western and eastern populations of L. m. samuelis . This supports the hypothesis that the presence of L. m. melissa mitochondrial haplotypes in western L. m. samuelis populations is the result of mitochondrial introgression. These data provide valuable information for conservation and management plans for the endangered L. m. samuelis , and illustrate the risks of using data from a single locus for diagnosing significant units of biodiversity for conservation.